1988
DOI: 10.1083/jcb.106.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine secretory granules and neuronal synaptic vesicles have three integral membrane proteins in common.

Abstract: Abstract. In response to an external stimulus, neuronal cells release neurotransmitters from small synaptic vesicles and endocrine cells release secretory proteins from large dense core granules. Despite these differences, endocrine cells express three proteins known to be components of synaptic vesicle membranes. To determine if all three proteins, p38, p65, and SV2, are present in endocrine dense core granule membranes, monoclonal antibodies bound to beads were used to immunoisolate organelles containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 33 publications
14
92
2
Order By: Relevance
“…This observation is, however, not at variance with the data presented here since the lower density of p38 per mg of membrane protein (about 20 times) in chromaffin vesicles would reduce the number of gold particles per cross-section of vesicle to background levels. The present results are suited to explain the recent finding that chromaffin vesicles can be bound to p38 antibody-coated beads [8]. Clearly, 20 molecules of p38 per vesicle would be sufficient to bind chromaffin vesicles as well as clear (synaptic) vesicles to such beads.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This observation is, however, not at variance with the data presented here since the lower density of p38 per mg of membrane protein (about 20 times) in chromaffin vesicles would reduce the number of gold particles per cross-section of vesicle to background levels. The present results are suited to explain the recent finding that chromaffin vesicles can be bound to p38 antibody-coated beads [8]. Clearly, 20 molecules of p38 per vesicle would be sufficient to bind chromaffin vesicles as well as clear (synaptic) vesicles to such beads.…”
Section: Resultssupporting
confidence: 67%
“…Recently it has been reported [8] that p38/synaptophysin also occurs in hormone containing large dense core vesicles. This would imply that p38/synaptophysin could fulfill similar functions…”
Section: Introductionmentioning
confidence: 99%
“…Synaptin/synaptophysin is a protein found in high concentrations in synaptic vesicles [5][6][7], and in lower concentration in large dense core vesicles and in endocrine vesicles like chromaffin granules [5,8,9]. Its consistent low levels in Alzheimer's (which is in agreement with immunohistochemical data [19,20]) and Pick's brains can simply be an expression of neuronal and synaptic loss occurring in these diseases, but a specific loss of synaptic vesicles should also be considered.…”
Section: Discussionmentioning
confidence: 56%
“…Synaptin/synaptophysin [4] is found in high concentrations in synaptic vesicles [5][6][7], but also in large dense core vesicles and endocrine vesicles [5,8,9]. Recently it has been reported that a monoclonal antibody against chromogranin A recognizes the characteristic plaques of Alzheimer's disease [10] indicating the presence of chromogranin immunoreactive material in these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…A neat explanation of the inverse frequency dependence of acetylcholine and VIP would be to suppose that the exocytosis of the VIP-rich vesicles occurs at a different site in the terminal (where L-type Ca*+-channels are concentrated) from that at which acetylcholine-rich synaptic vesicles undergo exocytosis and where N-type channels may be concentrated (Fig 3). It has been suggested (Geffen and Livett, 1971;Lowe et al, 1988) that in the adrenergic system the membranes of dense-cored vesicles, which contain the small-molecular-mass transmitter noradrenaline as well as neuropeptides are retrieved to form small, electron-lucent vesicles which are competent to take up and release noradrenaline and recycle in the terminal. It may be that this precursor-product relationship also exists, at least in cholinergic neurones of the guinea-pig myenteric plexus, between acetylcholine-containing, VIPrich storage particles and acetylcholine-rich synaptic vesicles, which, as we have seen, are able to recycle and thus to sustain acetylcholine release independently of axons1 transport.…”
Section: Gopurification Of Vip With Cholinergic Synaptosomesmentioning
confidence: 99%